The Influence of Brand Image, Brand Ambassador and Price on Purchasing Decisions for Scarlett Whitening Product in Riau - Elli Safika; Wan Junita Raflah (Politeknik Negeri Bengkalis, 2021)
This research aims to determine the influence and how much the influence of brand image, brand ambassador, and price on purchasing decisions for Scarlett Whitening Products in Riau partially and simultaneously. This research used quantitative methods. Data collection technique used online questionnaires and literature study with a sample of 97 people. The value of each independent variable is 2,888 for brand image; 2,135 for brand ambassador and 5,708 for price, meanwhile the value of t table is 1.986 that’s mean the brand image, brand ambassador, and price has significant and positive influence on purchasing decisions. The results of the coefficient of determination is 0,420 or 42%, which means the influence of the independent variable (brand image, brand ambassador, and price) on the dependent variable (purchasing decisions) is 42% while the remaining 58% is influenced by other factors not examined in this research.